The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1750-2659.2010.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality attributable to pandemic influenza A (H1N1) 2009 in San Luis Potosí, Mexico

Abstract: Please cite this paper as: Comas‐García et al. (2011) Mortality attributable to pandemic influenza A (H1N1) 2009 in San Luis Potosí, Mexico. Influenza and Other Respiratory Viruses 5(2), 76–82. Background  Acute respiratory infections are a leading cause of morbidity and mortality worldwide. Starting in 2009, pandemic influenza A(H1N1) 2009 virus has become one of the leading respiratory pathogens worldwide. However, the overall impact of this virus as a cause of mortality has not been clearly defined. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(71 reference statements)
1
11
1
Order By: Relevance
“…Two other UK studies were reported-in the England-only study, the estimated number of deaths was 390-490 25 and in the study of only England and Wales the estimate was 1556. 44 In one of the two studies from Mexico, the estimated mortality was 35 per 100 000 people in San Luis Potosi, 40 whereas in the other study the estimate was 6200 deaths for Mexico based on excess pneumonia and infl uenza mortality or 26 500 deaths based on excess all-cause mortality. 17 According to the estimates from two studies that included deaths in 2009 only, there were 6000 deaths in Bangladesh 45 and 0-256 deaths in Hong Kong, equal to an age-standardised mortality of 2•9-14•8 per 100 000 individuals.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other UK studies were reported-in the England-only study, the estimated number of deaths was 390-490 25 and in the study of only England and Wales the estimate was 1556. 44 In one of the two studies from Mexico, the estimated mortality was 35 per 100 000 people in San Luis Potosi, 40 whereas in the other study the estimate was 6200 deaths for Mexico based on excess pneumonia and infl uenza mortality or 26 500 deaths based on excess all-cause mortality. 17 According to the estimates from two studies that included deaths in 2009 only, there were 6000 deaths in Bangladesh 45 and 0-256 deaths in Hong Kong, equal to an age-standardised mortality of 2•9-14•8 per 100 000 individuals.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…We identifi ed 12 studies from eight countries in Europe, the Americas, western Pacifi c, and Asia. 14,17,23,25,[39][40][41][42][43][44][45][46] In two studies from Australia (New South Wales) 42 and the UK, 41 no deaths were estimated based on the excess all-cause mortality during periods of infl uenza virus circulation. Two other UK studies were reported-in the England-only study, the estimated number of deaths was 390-490 25 and in the study of only England and Wales the estimate was 1556.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…COPD refers to chronic obstructive pneumonia disease. IHD refers to ischemic heart disease (Simmerman et al [ 10 ], Wong et al [ 23 ], Comas-Garcia et al [ 24 ], Freitas et al [ 25 ], Charu et al [ 26 ], Wu et al [ 27 ], Oliveira et al [ 28 ], Chow et al [ 29 ], Wong et al [ 30 ], Lee et al [ 31 ], Ho and Chow [ 32 ], Yang et al [ 33 ], Li et al [ 13 ], Freitas et al [ 34 ])
Fig. 4 Influenza-associated mortality rates during the year of 2009 and after when A(H1N1)pdm09 virus circulated.
…”
Section: Influenza Burden In the Tropicsmentioning
confidence: 99%
“…The asterisk indicates a study period that did not cover an entire season or year. IHD refers to ischemic heart disease (Wu et al [ 35 ], Freitas et al [ 25 ], Echevarria-Zuno et al [ 20 ], Charu et al [ 26 ], Homaria et al [ 36 ], Cerbino Neto et al [ 37 ], Fowlkes et al [ 38 ], Wu et al [ 27 ], Perez-Flores et al [ 39 ], Comas-Garcia et al [ 24 ], Fajardo-Dolci et al [ 40 ], Saborio et al [ 19 ], Yang et al [ 33 ], Bunthi et al [ 41 ]) …”
Section: Influenza Burden In the Tropicsmentioning
confidence: 99%
“…Many patients had severe pneumonia related to influenza A(H1N1)pdm09 virus; the death rate was higher in Mexico than in most countries ( 3 5 ). …”
mentioning
confidence: 99%